Cardioprotective Effect of Low Molecular Weight (Below 5 kDa) Fraction of Cattle Cord Blood Cryohemolysate - Shcheniavsky, Ivan; Kovalenko, Igor; Gulevsky, Oleksandr (Problems of Cryobiology and Cryomedicine, 2022)
In this report, we have studied a cardioprotective effect of low molecular weight (below 5 kDa) fraction derived from cattle cord blood in a rat model of infarction-like cardiovasopathy. The myocardial infarction development was initiated in the animals, maintained for two months on a diet with excessive intake of fat, calcium and sodium salts, by making hypoxia-hypercapnia in them. The use of this model allowed inducing the infarction-like cardiovasopathy, comparable by many respects with the clinical picture of myocardial infarction, which was confirmed by electrocardiography, enzyme-linked immunosorbent assay and histological analysis. Preliminary administration of low molecular weight (below 5 kDa) fraction of cattle cord blood, as well as Actovegin did not prevent the heart attack, but increased the endurance of rats to hypoxia-hypercapnia and reduced the damage rate to myocardium. A preventive administration of low molecular weight fraction of cord blood was proven to mitigate the risk of hypoxia-induced damages to myocardium. Probl Cryobiol Cryomed 2022; 32(3):206–213